Generation electricity with hybrid energy (solar and wind energy) in Iran: A Review - Makkiabadi, Mahmoud (Technium Electro, 2024)
Generating electricity in Iran with fossil energy is much more than the usage of renewable energy. Iran is one of the leading non-renewable energy producers in the world due to its plentiful fossil fuel resources. The utilization of natural gas and petroleum in transportation and industrial sectors has been developed vastly in Iran because of their low prices. Consequently, the increasing rate of pollutant formation and depletion of non-renewable fuels have emerged as new challenges in the energy scenario of this country. The utilization of renewable resources is growing, in part due to the environmental impacts caused by fossil fuels. The most significant sources of renewable energy are wind, and solar and many predict that these energy sources will be used increasingly for distributed generation. In this paper, a review study of electricity generation by using solar and wind energy by 2020 is presented.